Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan PT. Gudang Garam Tbk. Pada Periode 2020-2022 - Muhammad Nurtajudin; Iswati Iswati; Anis Fitriyasari; Eny Sulistyowati (Manajemen Kreatif Jurnal, 2024)
In this research the author wants to know more about "Financial Ratio Analysis to Assess the Performance of PT. Gudang Garam Tbk. In the 2020-2022 Period”. Regarding the author's desire to analyze this company because since the Covid-19 outbreak occurred, all shares in cigarette industry companies in Indonesia have decreased, so with this research the author wants to examine one of the largest cigarette companies in Indonesia, namely PT. Gudang Garam Tbk. The method used by the author in the research is quantitative. The analytical method used is analysis of liquidity, solvency, activity and profitability ratios. Research data and information were obtained from the Indonesia Stock Exchange which can be accessed via the official website www.idx.co.id The data collection technique used was analyzing or calculating PT Gudang Garam Tbk Financial Report data. Data processing is carried out descriptively quantitatively, namely using the financial ratio formula, namely Liquidity Ratio, Solvency Ratio, Activity Ratio and Profitability Ratio to analyze existing problems based on financial reports at PT. Gudang Garam Tbk. 2020-2022 period.